A Case Report on Blood in Breastmilk: Safety Issues and Islamic Ruling - Jamani, NA; Mohamad, Hasbullah (IIUM Medical Journal Malaysia, 2018)
This case study demonstrates a 33-year old nursing mother who had noticed that her breastmilk had traces of blood giving the appearance of a strawberry coloured milk while expressing for her infant. This is an uncommon encounter but important issue to raise concern among Muslim nursing mothers in terms of medical safety and Islamic ruling of the standpoint of legal theorists (usul al-fiqh) and legal maxim (qawai’id fiqhiyyah).